The Qualifications and Views of Instructors in the Distance Education System - Blerta Prevalla Etemi (Kassel University Press, 2021)
A new process has been brought about due to the COVID-19 pandemic that has affected the world. Due to the COVID-19 pandemic, since the spring semester of the 2019–2020 academic year, all education and courses are provided through distance education. Therefore, since distance education is a new process for many, faculty members may encounter various problems. For this reason, deter-mining the views of lecturers about the distance education process is important for the improvement and development of the distance education system. The aim of this study is to examine the views of the lecturers who teach through the dis-tance education system and to make suggestions for the improvement of the sys-tem. The situation was determined using the qualitative research method. The re-search questions were prepared by the researchers. Their validity was ensured by taking experts’ opinions. For this purpose, interviews with semi-structured ques-tions were conducted with 28 instructors at Cyprus and Russian universities and the data obtained were evaluated by content analysis. The findings obtained as a result of the research are given in detail in the findings and results section.